A measure of entrepreneurial bricolage behavior. Issue 1 (9th January 2017) - Davidsson, Per; Baker, Ted; Senyard, Julienne Marie
Abstract : Purpose: The majority of emerging and young firms work under resource constraints. This has made researchers highlight the importance of resourcefulness. Perhaps the most important theoretical development in this context is the emerging, behavioral theory of entrepreneurial bricolage. However, although academic interest is increasing, research on entrepreneurial bricolage has been hampered by the lack of robust instruments that allow large-scale theory testing. The purpose is to help fill this void. The purpose of this paper is to describe the development and contents of a novel measure of entrepreneurial bricolage behavior and assesses its validity. The measure is intended to be applicable in broadly based, quantitative studies. Design/methodology/approach: The instrument was developed as a unidimensional, reflective measure. Standard protocols for scale development were followed. The validation uses primary, longitudinal data from four samples of nascent and young firms as well as published, cross-sectional evidence from another four samples representing different contexts and variations to the data collection procedure. Findings: Promising results are reported concerning the reliability as well as the discriminant and nomological validity of the measure. Based on the pre-testing and validation experiences guidelines are also provided for attempts at further improvements. Originality/value: This paper presents a novel measure developed by the authors, which holds promise for being a useful tool for future research on the prevalence, antecedents, and consequences of entrepreneurial bricolage. Previously, no established measure of entrepreneurial bricolage behavior existed, and the few partial measures appearing in the literature have not been comprehensively evaluated. Thus, we offer a comprehensive and elaborate presentation of a measure only briefly introduced in Davidsson (2016) and Senyard et al., (2014).